Effectiveness of teriparatide combined with the Ilizarov technique in septic tibial non-union - Giuseppe Rollo; Francesco Luceri; Gabriele Falzarano; Carlo Salomone; Enrico Maria Bonura; Dmitry Popkov; Mario Ronga; Giuseppe Pica; Michele Bisaccia; Valentina Russi; Predrag Grubor; Raffaele Franzese; et al. (Medicinski glasnik, 2020)
Aim: The septic non-union is a common compliance in bone healing due to bone infection. Bone resection, associated with Ilizarov osteo-distraction technique, is commonly used in these cases. The aim of this study was to analyse clinical and radiological results of teriparatide in combination with the Ilizarov technique and to compare this treatment with the standard treatment. Methods: Forty adult patients underwent surgery because of type C of the Association for the Study and Application of Methods: of Ilizarov (ASAMI) classification non-union were enrolled. The patients were divided in two groups: those treated with Ilizarov technique (Norm group) and those treated with Ilizarov technique combined with teriparatide injection (Teri group). Surgical duration, complication rate, bone healing status, clinical and functional outcomes were assessed according to the A.S.A.M.I. classification in the mean follow-up of 12 months. The subjective quality of life was assessed by the Short Form Survey (SF)-12. Results: Teri group showed less time wearing Ilizarov's frame (p<0.05) than the Norm group and a statistical significance in the inter-rater reliability Cohen’s k (p>0.05) respect to Norm according the score between the bone healing and clinical outcome results. There was no statistically significant difference between the two groups in other parameters that were assessed. Conclusion: A benefit of teriparatide was found as adjuvant in the treatment of septic non-union.
Keywords: bone regeneration; Ilizarov technique; teriparatide; tibia; limb salvage; osteomyelitis